The Students’ Perspective towards Orderly Rows Seating Arrangements in Higher Level Education - Vanny Handayani (Concept : Community Concern for English Pedagogy and Teaching, 2020)
The notion of setting effective seating arrangements has been reviewed in some research related to classroom management strategies. In practice, seating arrangement can be one of the most important aspects that can create a positive learning environment in the classroom. However, considering effective classroom management and setting effective seating arrangements are often neglected by the teachers in their teaching preparation. This research was conducted to investigate the students’ perspectives toward orderly rows seating arrangements in higher level education. In this study, three main instruments were used to collect the data namely interview, observation, and questionnaire. Based on the results of the study, it is found that the use of orderly rows seating arrangements in the classrooms has some advantages and disadvantages. In some circumstances, orderly rows seating arrangement is best applied for doing presentation, lecture, or explanation. Unless, it is less effective for several reasons such as it tends to have teacher-centered than student-centered learning; there are less of group discussions; and it diminishes the teacher or students’ movements. To review these findings, furthermore, it is suggested that the use of seating arrangements in the classrooms should vary set from orderly rows, circle, U-shape, horseshoe, to separate tables by using appropriate movable desk-chairs accustomed to the learning goals, needs, methods, and classroom situation. Keywords: orderly rows seating arrangement; classroom management